Kemampuan Adaptasi Dan Komunikasi Mahasiswa Perantau Di Wonogiri - Hernawati, Hernawati; Sujiono, Sujiono; Setyoko, Rahmad (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Migrant students often have difficulty understanding the culture and language of local students. So that students anxious when meeting and interanting directly with students on the STAB Negeri Raden Wijaya Wonogiri campus. The adaptability and communication skills of migrant students are relatively low due to the cultural differences between migrant students and local environment. This research aims to analyze the adaptation and communication skills of migrant students in Wonogiri. In this research, researchhers used quantitative methods and the research was designed as explanatory survey research. The results of the research show that overseas students are able to interact and communicate with local students who of course have different cultures. Apart from that, as long as migrant students adapt and communicate, migrant students learn a lot about the culture that exists in the STAB Negeri Raden Wijaya Wonogiri campus environment and they learn that adaptation and communication are really needed when they in a new living environment. The statistical test results show that each categories shows a high category and percentage.